The Interwoven of interests in Political Economy and Political Behavior of Women Members of Parliament - Dewi Komalasari (Yayasan Jurnal Perempuan, 2019)
The representation of women’s interest through women Members of Parliament (MPs) is achieved if there is a connection between constituents and parliamentarians. In order to be able to establish cooperation, it requires a deep understanding of their behavior. This article reveals the variety of relationships and political economic affiliations that surround women MPs. The relationship has been built since the nomination period to become a member of parliament, which in turn raises various interests and pressures that women parliamentarians must respond to. By understanding the various interests and pressures faced by women MPs, civil society can design action plans that trigger positive responses so as to minimize the potential risks.